Differences The Evaluation of Media Below The Line for Increasing Larc Participation in Rural-Urban Regions - Muhammad Irwan Setiawan; Meitria Syahadatina Noor; Fakhriyah Fakhriyah; Oktriyanto Oktriyanto (Jurnal Berkala Kesehatan, 2022)
The Long-Acting Reversible Contraceptive Method (LARC) is one of the flagship programs of the Population and Family Planning Agency (BKKBN) for controlling pregnancy. The use of LARC is still very low in Indonesia, where South Kalimantan is the province with the lowest coverage. The purpose of this study is to evaluate the effectiveness of IEC media to increase LARC family planning participation for fertile age couple (FEC) in urban and rural areas. Quantitative research with a survey approach was carried out on women who did not use LARC contraception. The study was conducted for 7 months with a total sample of 266, consisting of 173 urban and 93 rural. The media below the line (BTL) evaluation consists of booklets, leaflets, and Balinese sheets with 4 dimensions: empathy, persuasion, impact, and communicativeness. Mann Whitney test was performed to analyze the difference in the effectiveness of BTL media between urban vs rural with a significance value of p<0.05. The effectiveness of BTL media has a significant difference between urban areas and rural, where the highest score is in the Galcitas area with median score (min-max) of 12 (10-15). BTL media has a very high effectiveness on FEC's decision to use the LACR.